2017
DOI: 10.1136/bmjopen-2017-017471
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between marine omega-3 supplement users and coronary heart disease in a UK population-based cohort

Abstract: ObjectivesAssess the association between marine omega-3 polyunsaturated fatty acid (n-3 PUFA) intake from supplements, mainly cod liver oil, and coronary heart disease (CHD) mortality.DesignProspective cohort study, with three exposure measurements over 22 years.SettingNorfolk-based European Prospective Investigation into Cancer (EPIC-Norfolk, UK).Participants22 035 men and women from the general population, 39–79 years at recruitment.ExposureSupplement use was assessed in three questionnaires (1993–1998; 2002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The confounding associated with SU + EPA/DHA and SU − EPA/DHA as well as the changes over time in supplement use was modelled using time-varying covariates analysis. It was observed that CHD mortality was 26 % lower (95 % CI 16, 34 %) among SU + EPA/DHA compared with NSU, but no significant association was observed when comparing SU − EPA/DHA v. NSU ( 106 ) . Due to the observational nature of the study, residual confounding and colinearity of nutrients could have occurred.…”
Section: Health Outcomesmentioning
confidence: 96%
“…The confounding associated with SU + EPA/DHA and SU − EPA/DHA as well as the changes over time in supplement use was modelled using time-varying covariates analysis. It was observed that CHD mortality was 26 % lower (95 % CI 16, 34 %) among SU + EPA/DHA compared with NSU, but no significant association was observed when comparing SU − EPA/DHA v. NSU ( 106 ) . Due to the observational nature of the study, residual confounding and colinearity of nutrients could have occurred.…”
Section: Health Outcomesmentioning
confidence: 96%
“…was the most popular supplement (consumed by 32% of men and 45% of women) (10) . However, it is worth noting that over-the-counter fish oil preparations do not always contain the dose advertised on the label, and that the fatty acids can often be extensively oxidised, compromising their proposed biological function (11,12) .…”
Section: Dietary Sources Of Long Chain Omega-3 Polyunsaturated Fatty mentioning
confidence: 99%
“…While the average oily fish intake falls alarmingly short of this 140 g recommendation, also noteworthy is the median intake for both age groups is 0 g per week, with the majority of UK adults avoiding dietary intake of oily fish altogether. Evidence from the EPIC-Norfolk study highlights that cod liver oil (a source of n -3 PUFA) was the most popular supplement consumed by 32 % of men and 45 % of women (10) . However, it is worth noting that over-the-counter fish oil preparations do not always contain the dose advertised on the label, and that the fatty acids can often be extensively oxidised, compromising their proposed biological function (11,12) .…”
Section: Dietary Sources Of Long-chain N-3 Pufamentioning
confidence: 99%
“…39 A 22 year study of > 20,000 patients found that OM3 supplementation was associated with a lower hazard of CHD mortality. 40 The JELIS trial in Japan…”
Section: Coronary Heart Diseasementioning
confidence: 99%